Study on Producing Hydrogen by Catalytic Pyrolysis of Coal Slime - Zhang, Lei; Wang, Hao; Shu, Xinqian (Asian Journal of Chemistry, 2012)
This paper mainly focused on the law of flammable hydrogen-rich gas by coal slime pyrolysis. In order to increase the production of hydrogen, this experiment added different n-type metal-oxide and alkali metal oxide as catalyst in the process of pyrolysis. It provided an effective and reliable method of clean and efficient utilization of coal slime. Experiments showed that the catalytic activity was very low from room temperature to 600 ºC, no matter added catalyst or not the yield of hydrogen was very little. But in high-temperature range (600-1100 ºC), catalyst showed different catalytic effect. In 600-800 ºC temperature region, CaO showed the strongest catalytic effect. It is not only to increase the yield and output of hydrogen, but also plays a significant role to improve the yield of CO, the yield of the CO could increased from 3.85 to 21.24 %. In the high temperature range of 800-1100 ºC, n-type semiconductor catalyst shown a good catalytic effect, especially Fe2O3 catalyst increased the yield of hydrogen from 56.51 to 82.06 % at 1100 ºC, the total output can also increase twice.